An Interdisciplinary study of the cinematic adaptation of “Lonesome Trees” by Houshang Moradi Kermani - maryam esmaili (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
One of the areas of research in comparative literature is the study of the relationship between literature and cinema. This research analyses the adaptation process of “Lonesome Trees” (by Houshang Moradi Kermani) in its cinematic adaptation (directed by Saeed Ebrahimifar), from the perspective of literary adaptation. The goal of this paper is to study and analyze the changes that have taken place during the adaptation process. The theoretical framework of this research is based on A Theory of Adaptation by Linda Hutcheon. Hutcheon believes that adaptation is an active and meaning making process in which the adapter interacts with the text as a reader. The result of this reading is a creative interpretation which is the product of the adapter’s mindset. Therefore, loyalty is not the evaluation criterion for a cinematic adaptation. In this paper, we demonstrate how and why, as a director and an adaptor, Saeed Ebrahimifar creates a unique narrative independent from Moradi Kermani’s “Lonesome Trees” a work which has significant differences from the original text.